PENGARUH PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN KACAMATA PADA AGUNG OPTIK DI KOTA PALU - Tini, Tini (Fakultas Ekonomi Universitas Tadulako, 2019)
The purpose of this study was to determine the effect of simultaneous and partial personal selling on the decision to buy glasses at Agung Optik in Palu city. The independent variable used in this study is personal selling (X) while the dependent variable is the purchase decision (Y). The research method used in this study is a descriptive causal sample method used in this study as many as 90 respondents with the form of sampling using purposive sampling technique. Data analysis method used in this study is a multiple linear regression analysis method. The results of this study indicate that: 1). Simultaneously personal selling has a significant influence on the decision to buy glasses at Agung Optik in Palu city. 2). Approach variables, presentation and demonstration, handling objections, closing, and follow-up partially have a significant effect on the decision to purchase glasses at Agung Optik in Palu city.